Composite solid electrolyte for all-solid-state battery, manufacturing method thereof, electrode and all-solid-state battery using the same

KR103035586B1Active Publication Date: 2026-10-21KNU IND COOPERATION FOUND
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
KR1020240191208
Authority / Receiving Office
KR · KR
Patent Type
Patents
Current Assignee / Owner
Priority Date
2024-01-17
Filing Date
2024-12-19
Publication Date
2026-10-21
Estimated Expiration
2044-12-19

Smart Images

  • Figure 112024141284279-PAT00001_ABST
    Figure 112024141284279-PAT00001_ABST
Patent Text Reader

Abstract

The present invention relates to a solid electrolyte for an all-solid-state battery, and more specifically, to a composite solid electrolyte for an all-solid-state battery, a method for manufacturing the same, an electrode using the same, and an all-solid-state battery, wherein by manufacturing a carbon / oxide-based composite solid electrolyte, a smooth electron conduction path within the electrode can be secured, and effects such as a reduction in the content of the solid electrolyte, an increase in the fraction of the active material, an improvement in the internal resistance of the electrode, and an improvement in the life characteristics of the all-solid-state battery can be exhibited. To this end, a method for manufacturing a composite solid electrolyte for an all-solid-state battery comprises the steps of: preparing a mixed solution containing a lithium salt, a lanthanum salt, a zirconium salt, a carbon material, and a solvent; treating the mixed solution with microwaves to prepare a precursor solution; centrifuging the precursor solution; drying and grinding the precipitate obtained after centrifugation to prepare a precursor powder; and calcining the precursor powder to prepare a carbon / oxide-based composite solid electrolyte.
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] The present invention relates to a solid electrolyte for an all-solid-state battery, and more specifically, to a composite solid electrolyte for an all-solid-state battery, a method for manufacturing the same, an electrode using the same, and an all-solid-state battery, wherein by manufacturing a carbon / oxide-based composite solid electrolyte, a smooth electron conduction path within the electrode can be secured, and effects such as a reduction in the content of the solid electrolyte, an increase in the fraction of the active material, an improvement in the internal resistance of the electrode, and an improvement in the lifespan characteristics of the all-solid-state battery can be exhibited. Background Technology

[0003] Currently commercialized lithium-ion batteries are used in various fields due to their advantages, such as excellent energy density and long lifespan. Recently, as their application scope is gradually expanding to include energy storage systems (ESS) and electric vehicles (EVs), the demand for high-performance batteries—including high output, high capacity, and high safety—is increasing day by day.

[0005] Conventional lithium-ion batteries use organic liquid electrolytes, posing safety risks due to the potential for leakage and ignition. These safety issues are becoming increasingly serious as battery capacities increase and demand grows. Consequently, active research is currently being conducted on all-solid-state batteries utilizing non-combustible inorganic solid electrolytes to overcome these existing safety concerns.

[0007] Solid electrolytes can be broadly classified into sulfide-based and oxide-based types; however, sulfide-based solid electrolytes react with moisture in the atmosphere, making it very difficult to control the process environment. Furthermore, they have the disadvantage of poor compatibility with anodes that primarily use oxides and the occurrence of side reactions at the interface with the electrode.

[0009] In contrast, oxide-based solid electrolytes not only possess high stability in moisture and atmosphere, but also exhibit excellent chemical and electrochemical stability. Li7La3Zr2O is one such oxide-based solid electrolyte. 12 (LLZO) is 10 -3 It has high ionic conductivity among oxide systems, at approximately S / cm, so much research is currently being conducted on it.

[0011] However, simply replacing liquid electrolytes with solid electrolytes like the one above does not easily meet the requirements for high-performance batteries currently demanded.

[0012] All-solid-state batteries generally contain an excess amount of solid electrolyte of more than 10 wt% in the electrode to compensate for low interface characteristics, which can result in a lower fraction of active material compared to conventional batteries, and this leads to a lower energy density of the battery.

[0014] Therefore, to increase the energy density of all-solid-state batteries, in addition to using high-performance active materials, research on reducing and optimizing the content of inactive components, such as solid electrolytes and conductive materials, is essential. Prior art literature

[0016] Republic of Korea Registered Patent Publication No. 10-2457705 The problem to be solved

[0017] The present invention aims to solve the above-mentioned problems by manufacturing a carbon / oxide-based composite solid electrolyte, thereby lowering the internal resistance of the electrode and providing a continuous conduction path to ensure smooth ion supply, which minimizes the voids in the electrode, thereby enabling effects such as reducing the solid electrolyte content and improving the fraction of the active material. The invention provides a composite solid electrolyte for an all-solid-state battery, a method for manufacturing the same, an electrode using the same, and an all-solid-state battery.

[0019] The above and other objects and advantages of the present invention will become apparent from the following description describing preferred embodiments. means of solving the problem

[0021] The above objective can be achieved by a method for manufacturing a composite solid electrolyte for an all-solid-state battery, comprising the steps of: preparing a mixed solution containing a lithium salt, a lanthanum salt, a zirconium salt, a carbon material, and a solvent; microwave-treating the mixed solution to prepare a precursor solution; centrifuging the precursor solution; drying and grinding the precipitate obtained after centrifugation to produce a precursor powder; and calcining the precursor powder to produce a carbon / oxide-based composite solid electrolyte.

[0022] The above carbon material is characterized by comprising one or more selected from the group consisting of carbon nanotubes (CNT), acid-treated carbon nanotubes (Acid-treated CNT), vapor-grown carbon fibers (VGCF), carbon nanofibers (CNF), carbon nanowires (CNW), doped carbon nanowires (N-doped CNW), carbon nanoribbons, graphene, carbon nanofiber (CNF) hybrid graphene, and carbon nanotube (CNT) hybrid graphene, Super-P, Super-C, natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, furnace black, lamp black, and thermal black.

[0023] The above mixed solution comprises a solvent and further comprises one or more selected from a complexing agent, a pH adjuster, and a chelating agent, wherein the chelating agent comprises citric acid.

[0024] In addition, the above-mentioned mixed solution is characterized by further including an oxygen removal agent.

[0025] The above microwave treatment is characterized by being performed at a power of 380 to 420 W at 210 to 280°C for 8 to 15 minutes. The above centrifugation is characterized by being performed at a speed of 10,000 rpm or more for 1 hour or more.

[0026] The above calcination is characterized by comprising: a step of performing a first heat treatment at a temperature of 360°C or higher for 5 hours or more at a heating rate of 10°C / min or more in an air atmosphere; and a step of performing a second heat treatment at a temperature of 900°C or higher for 5 hours or more at a heating rate of 5°C / min or more in an inert atmosphere.

[0027] The above objective can be achieved by a composite solid electrolyte for an all-solid-state battery manufactured according to the method for manufacturing a composite solid electrolyte for an all-solid-state battery.

[0028] The above-described composite solid electrolyte for an all-solid-state battery is characterized as a carbon / oxide-based composite solid electrolyte having a composite structure in which particles of an oxide-based component are distributed on the surface of a carbon-based component having a predetermined length and thickness.

[0029] The above objective can be achieved by an electrode for an all-solid-state battery manufactured by an electrode composition comprising a carbon / oxide-based composite solid electrolyte and an active material.

[0030] The above objective can be achieved by an all-solid-state battery comprising: a solid electrolyte layer comprising a carbon / oxide-based composite solid electrolyte; an anode layer laminated on one side of the solid electrolyte layer; and a cathode layer laminated on the other side opposite to one side of the solid electrolyte layer, wherein at least one of the anode layer and the cathode layer is manufactured by an electrode composition comprising the carbon / oxide-based composite solid electrolyte of claim 8. Effects of the invention

[0032] According to the present invention, a carbon / oxide-based composite solid electrolyte can be manufactured and applied in place of the solid electrolyte and conductive material in the anode.

[0034] The carbon / oxide-based composite solid electrolyte according to the present invention can lower the internal resistance of the electrode and provide a continuous conduction path by using a carbon material with a high aspect ratio, and can further improve electron conductivity by effectively interlocking with the active material.

[0036] According to the present invention, by combining a carbon material capable of providing an electron conduction path with LLZO, which exhibits excellent ion conductivity among oxide-based solid electrolytes, smooth ion supply from the solid electrolyte distributed in the carbon network is made possible. In addition, the voids of the electrode can be minimized in the process, thereby reducing the content of the solid electrolyte and improving the fraction of the active material.

[0038] According to the present invention, a carbon / oxide-based composite solid electrolyte synthesized by a simple process can secure an electrode with improved internal resistance by effectively transferring electrons and ions through an increased contact area between the solid electrolyte and the active material, and between the conductive material and the active material, during the charge-discharge process. Furthermore, it can exhibit the effect of improving the lifespan characteristics of next-generation all-solid-state batteries.

[0040] However, the effects of the present invention are not limited to those mentioned above, and other unmentioned effects will be clearly understood by those skilled in the art from the description below. Brief explanation of the drawing

[0042] FIG. 1 is a flowchart showing the steps of a method for manufacturing a composite solid electrolyte according to one embodiment of the present invention. Figure 2 is a graph showing the X-ray diffraction (XRD) analysis results of a composite solid electrolyte prepared according to Example 1 of the present invention. Figure 3 is a graph showing the results of the Raman spectrum analysis of a composite solid electrolyte prepared according to Manufacturing Example 1 of the present invention. Figure 4 is a graph showing the X-ray photoelectron spectroscopy (XPS) analysis results of a composite solid electrolyte prepared according to Manufacturing Example 1 of the present invention. Figure 5 is a scanning electron microscope (SEM) analysis image of a composite solid electrolyte prepared according to Manufacturing Example 1 of the present invention. Figure 6 is an energy dispersive X-ray spectroscopy (EDS) analysis image of a composite solid electrolyte prepared according to Preparation Example 1 of the present invention. Figure 7 is a transmission electron microscope (TEM) analysis image of a composite solid electrolyte prepared according to Example 1 of the present invention. Specific details for implementing the invention

[0043] The present invention will be described in detail below with reference to the embodiments and drawings. These embodiments are presented merely as examples to explain the invention more specifically, and it will be obvious to those skilled in the art that the scope of the invention is not limited by these embodiments.

[0044] Furthermore, unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art to which the present invention pertains, and in the event of a conflict, the description in this specification, including the definitions, shall prevail.

[0045] To clearly explain the proposed invention in the drawings, parts unrelated to the description have been omitted, and similar parts throughout the specification have been given similar reference numerals. Furthermore, when a part is described as "comprising" a certain component, this means that, unless specifically stated otherwise, it does not exclude other components but may include additional components. Additionally, the term "part" as described in the specification refers to a single unit or block that performs a specific function.

[0046] In each step, identification codes (1st, 2nd, etc.) are used for convenience of explanation and do not describe the order of the steps; the steps may be performed differently from the specified order unless a specific order is clearly indicated in the context. That is, the steps may be performed in the same order as specified, substantially simultaneously, or in the reverse order.

[0048] Hereinafter, embodiments and examples of the present invention will be described in detail with reference to the attached drawings. However, the present invention may not be limited to these embodiments and examples and drawings.

[0050] Carbon / Oxide-based Composite Solid Electrolytes

[0051] A carbon / oxide-based composite solid electrolyte according to one embodiment of the present invention is used in an all-solid-state lithium secondary battery, and specifically, may be a composite of a carbon-based component and an oxide-based component.

[0053] Specifically, the above oxide-based component is lithium lanthanum zirconium oxide (Li7La3Zr2O) having a garnet structure. 12 It may be )(hereinafter referred to as LLZO) or cation-doped LLZO, such as gallium (Ga)-doped LLZO (hereinafter referred to as Ga-LLZO).

[0054] The above oxide-based component exhibits characteristics such as high ionic conductivity, high stability with lithium metal, and a wide potential window range, making it desirable for application as a solid electrolyte in all-solid-state batteries.

[0055] The above carbon-based component may include one or more selected from the group consisting of carbon nanotubes (CNT), vapor-grown carbon fibers (VGCF), carbon nanofibers (CNF), carbon nanowires (CNW), doped carbon nanowires (N-doped CNW), carbon nanoribbons, graphene, carbon nanofiber (CNF) hybrid graphene, and carbon nanotube (CNT) hybrid graphene, Super-P, Super-C, natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, furnace black, lamp black, and thermal black.

[0056] For example, the carbon-based component may include carbon nanotubes (CNT) or acid-treated carbon nanotubes (Acid-treated CNT).

[0057] The length of the carbon nanotube (CNT) or acid-treated carbon nanotube (Acid treated CNT) may be, for example, 2 nm to 1000 μm, and the thickness may be 0.5 nm to 1000 nm.

[0058] Preferably, the aspect ratio of the carbon nanotube (CNT) or acid-treated carbon nanotube (Acid-treated CNT) may be, for example, 2 or more, 3 or more, 4 or more, 5 or more, 10 or more, 20 or more, 50 or more, or 100 or more.

[0059] When using the carbon nanotubes (CNT) or acid-treated carbon nanotubes (Acid-treated CNT) having a high aspect ratio as the carbon-based component, even if included in a low amount, they can be dispersed three-dimensionally to form a conductive network and improve electrical conductivity.

[0061] The carbon / oxide-based composite solid electrolyte of the present invention is a single material in which the oxide-based component and the carbon-based component are composited, specifically, it may have a structure in which particles of the oxide-based component are distributed entirely on the surface of a carbon-based component having a predetermined length and thickness.

[0062] In other words, in the present invention, by combining a carbon-based component capable of providing an electron conduction path with LLZO or Ga-LLZO, which exhibits excellent ion conductivity among existing oxide-based solid electrolytes, a smoother supply of ions from the solid electrolyte distributed in the carbon network can be achieved. In addition, the voids of the electrode can be minimized in the process, thereby reducing the content of the solid electrolyte and improving the fraction of the active material.

[0063] At this time, the carbon nanotube (CNT) as the carbon-based component has a high aspect ratio, which can lower the internal resistance of the electrode and continuously provide a continuous conduction path, and can further enhance the effect of improving electron conductivity by effectively intertwining with the active material.

[0064] For example, in the carbon / oxide-based composite solid electrolyte, the oxide-based component and the carbon-based component may have a mixing ratio of 1:0.5 to 1.1 by weight, specifically 1:0.8 to 1 by weight.

[0066] FIG. 1 is a flowchart showing the steps of a method for manufacturing a composite solid electrolyte according to one embodiment of the present invention.

[0067] Referring to FIG. 1, the method for manufacturing a composite solid electrolyte for an all-solid-state battery comprises the steps of: preparing a mixed solution containing a lithium salt, a lanthanum salt, a zirconium salt, a carbon material, and a solvent (S10); preparing a precursor solution by microwave treatment of the mixed solution (S20); centrifuging the precursor solution (S40); drying and grinding the precipitate obtained after centrifugation to produce a precursor powder (S50); and calcining the precursor powder to produce a carbon / oxide-based composite solid electrolyte (S60).

[0069] In the above S10 step, the mixed solution may include raw materials of lithium (Li), lanthanum (La), and zirconium (Zr), which are the main elements constituting the oxide-based components, and carbon materials, which are the raw materials of the carbon-based components. The mixed solution may further include raw materials of gallium (Ga), which is the doping element of the oxide-based components.

[0070] The above-mentioned raw material for Li may include one or more selected from the group consisting of, for example, Li2CO3, LiOH, and LiNO3 as lithium salts. For example, LiOH may be used as the lithium salt.

[0071] The raw material for the above La can be a lanthanum salt, for example, La(NO3)3 or La2O3. For example, La(NO3)3 can be used as the above lanthanum salt.

[0072] The raw material for the above zirconium (Zr) can be a zirconium salt, for example, ZrO(NO3)2 or ZrO2. For example, ZrO(NO3)2 can be used as the zirconium salt.

[0073] The raw material for the above gallium (Ga) can be a gallium salt, for example, Ga(NO3)3.

[0074] The aforementioned raw materials exhibit excellent stability among the precursors of each element, and thus can provide the advantage of being easy to handle during the weighing and mixing process.

[0076] The above carbon material may include one or more selected from the group consisting of carbon nanotubes (CNT), acid-treated carbon nanotubes (Acid-treated CNT), vapor-grown carbon fibers (VGCF), carbon nanofibers (CNF), carbon nanowires (CNW), doped carbon nanowires (N-doped CNW), carbon nanoribbons, graphene, carbon nanofiber (CNF) hybrid graphene, and carbon nanotube (CNT) hybrid graphene, Super-P, Super-C, natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, furnace black, lamp black, and thermal black, and these may be manufactured according to known technology or commercially available products commonly used.

[0077] The carbon material of the aforementioned example materials may also include, for example, at least one functional group selected from sulfate groups, carbonate groups, nitric acid groups, hydroxyl groups, phosphate groups, and carboxyl groups.

[0078] For example, the carbon material mentioned above may be carbon nanotubes (CNT), more specifically, acid-treated carbon nanotubes (Acid-treated CNT).

[0080] The above mixed solution includes a solvent and may further include one or more selected from a complexing agent, a pH adjuster, and a chelating agent.

[0081] The above complexing agent may include, for example, ammonia water or sodium hydroxide.

[0082] The above pH adjuster may include, for example, sodium hydroxide, ammonia, etc. The above pH adjuster can adjust the pH of the above mixed solution to, for example, 10 to 12.

[0083] The above chelating agent may be, for example, a compound having two or more carboxyl groups. Examples of the above chelating agent include citric acid, tartaric acid, ascorbic acid, etc., and specifically, it may be citric acid. The above chelating agent can increase stability in a mixed solution through a ligand exchange reaction with the raw materials of Li, Zr, and La.

[0084] The above solvent may be water or an organic solvent including ethanol, methanol, and diethylene glycol (DEG), etc.

[0085] For example, the above solvent may be diethylene glycol (DEG).

[0087] In addition to the aforementioned components, the above-mentioned mixed solution may further include additives or additional components commonly used in the field within a normal content range.

[0089] For example, the above mixed solution may further include an oxygen remover. Specifically, the oxygen remover may include one or more selected from organic germanium, guaiacol, grape skin extract powder, and honeysuckle extract powder.

[0090] The aforementioned components can help extend the lifespan of the battery by eliminating reactive oxygen species generated during charging and discharging. Even with the addition of only a small amount, they exhibit excellent antioxidant capacity, blocking the decomposition of the electrolyte and forming a protective film on the electrode, thereby effectively preventing structural changes or aging of the battery.

[0092] It is preferable that the oxygen remover be included in a range of 0.01 to 5 weight%, specifically 0.05 to 0.5 weight%, relative to the total weight of the mixed solution.

[0093] The oxygen scavenger included in the aforementioned components and content ranges can exhibit superior antioxidant capacity compared to conventional all-solid-state battery electrolytes without impairing the physical properties of the constituent components when manufacturing a carbon / oxide-based composite solid electrolyte.

[0095] In the above S20 step, the precursor solution can be prepared by microwave-treating the above mixed solution.

[0096] Through the above microwave treatment, sufficient energy can be provided to cause all components in the mixed solution to undergo complex crystallization.

[0097] Specifically, the above microwave treatment may be performed by introducing the mixed solution into a microwave container and stirring it, and using a microwave irradiation device, for example, at a power of 380 to 420 W, for example, 400 W, for example, at 210 to 280°C, for example, at 250°C, for example, for 8 to 15 minutes, for example, 10 minutes.

[0098] The method for preparing the above precursor solution is not particularly limited and may follow known techniques or be applied by modifying techniques known to those skilled in the art.

[0100] In the above S30 step, the precursor solution can be centrifuged.

[0101] The above centrifugation is preferably performed for at least 1 hour at a speed of 9,000 rpm or more, specifically 10,000 rpm or more, using a conventional centrifuge, for example. Through the above centrifugation, the precipitate and the supernatant can be separated.

[0102] When centrifugation is performed under the aforementioned conditions, it can help to manufacture carbon / oxide-based composites in the form of particles having a desired size. However, if centrifugation is performed outside of the aforementioned conditions, crystallization may not occur, making it impossible to manufacture the particles.

[0104] In the above S40 step, the precipitate obtained after centrifugation can be dried and ground to produce a precursor powder.

[0105] The above drying can be performed using a conventional drying apparatus, for example, by raising the drying temperature at a heating rate of 13 to 17°C / min, for example, 15°C / min, and then, for example, at a drying temperature of 250°C or higher for 2 hours or more. By performing drying under the aforementioned conditions, the drying efficiency can be increased and the remaining solvent (DEG) in the precipitate can be almost completely removed.

[0106] The dried material may be pulverized using a conventional grinding device. Specific grinding methods may follow known techniques commonly used in the relevant field.

[0108] In the above S50 step, the precursor powder can be calcined to produce a carbon / oxide-based composite.

[0109] The above calcination may be heat-treated once or two or more times.

[0110] For example, the calcination may include the step of performing a first heat treatment at a temperature of 360°C or higher for 5 hours or more at a heating rate of 10°C / min or more in an air atmosphere; and the step of performing a second heat treatment at a temperature of 900°C or higher for 5 hours or more at a heating rate of 5°C / min or more in an inert atmosphere.

[0111] Thus, a carbon / oxide-based composite (hereinafter referred to as CNT / LLZO or CNT / Ga-LLZO) according to one embodiment of the present invention can be manufactured in powder form. The composite solid electrolyte for an all-solid-state battery, specifically, the carbon / oxide-based composite solid electrolyte, can form a composite structure in which particles of an oxide-based component are distributed on the surface of a carbon-based component having a predetermined length and thickness. At this time, the particles of the oxide-based component may have a size of 100 nm or less.

[0112] The above carbon / oxide-based composite solid electrolyte can subsequently be manufactured in the form of a carbon / oxide-based composite solid electrolyte layer according to commonly used known techniques.

[0114] Meanwhile, an isosorbide film, which is an eco-friendly material, may be formed on at least one surface of the carbon / oxide-based composite solid electrolyte layer manufactured according to the disclosed technology. That is, a structural layer formed by laminating the carbon / oxide-based composite solid electrolyte layer and the isosorbide film layer may be used as a solid electrolyte.

[0115] The above isosorbide film is an eco-friendly material film made by processing plant resources such as corn, and it helps to optimize battery performance, reduce degradation, and increase lifespan and safety in the future, and can create synergy with the above carbon / oxide-based composite solid electrolyte layer to improve the performance and quality of the battery.

[0116] The method for manufacturing the above isosorbide film is not particularly limited and may follow known techniques or apply known techniques with any design modifications, provided that the physical properties of the entire solid electrolyte are not compromised.

[0117] For example, it is preferable that the thickness of the isosorbide film be formed to be 0.1 to 5%, specifically 0.5 to 3.5%, relative to the thickness of the carbon / oxide-based composite solid electrolyte layer.

[0119] Electrode for All-Solid State Batteries

[0120] An electrode for an all-solid-state battery according to one embodiment of the present invention may be based on a carbon / oxide-based composite solid electrolyte. Accordingly, the electrode for the all-solid-state battery may be manufactured using an electrode composition comprising a carbon / oxide-based composite solid electrolyte. Since the carbon / oxide-based composite solid electrolyte is identical to that described above, a detailed description thereof will be omitted here.

[0122] The electrode composition comprising the above carbon / oxide-based composite solid electrolyte may include an active material and a carbon / oxide-based composite solid electrolyte.

[0123] The above active material may be, for example, a positive electrode active material, a negative electrode active material, or a combination thereof.

[0124] The above positive electrode active material is, for example, lithium cobalt oxide (LiCoO2), lithium nickel oxide (LiNiO2), lithium manganese oxide (LiMnO2), lithium copper oxide (LiCoO2), lithium nickel-cobalt-manganese oxide (LiNi x Co y Mn z O2;NCM), lithium nickel-cobalt-aluminum oxide (LiNixCoyAlzO2;NCA), and lithium nickel-cobalt-manganese-aluminum oxide (LiNi x Co y Mn z Al (1-x-y-z) It may include at least one selected from O2;NCMA).

[0125] The above negative electrode active material may include at least one selected from non-graphitized carbon, graphite-based carbon, silicon-containing graphite-based carbon, lithium metal, lithium alloy, silicon-based alloy, tin-based alloy, polyacetylene, and Li-Co-Ni-based material.

[0126] In the above electrode composition, the active material and the composite solid electrolyte may be mixed in a weight ratio of 60 to 95: 5 to 40.

[0127] In addition to the aforementioned components, the electrode composition may further include, within an appropriate content range, additives commonly used in the field, such as electrochemical reaction aids, redox modifiers, oxygen scavengers, and stable SEI (solid electrolyte interphase) forming agents, for example, alkali metal salts, alkaline earth metal salts, or transition metal salts.

[0128] The above electrode can be formed by applying the electrode composition to an electrode current collector and pressing it by heat pressing or high pressure.

[0129] However, not limited thereto, electrodes for all-solid-state batteries can be manufactured according to known techniques commonly used in the field.

[0131] All-solid-state battery

[0132] An all-solid-state battery according to one embodiment of the present invention may include an electrode based on the carbon / oxide-based composite solid electrolyte. Since the electrode is identical to the one described above, a detailed description thereof will be omitted here.

[0134] Specifically, the all-solid-state battery comprises: a carbon / oxide-based composite solid electrolyte layer; a positive electrode layer laminated on one side of the carbon / oxide-based composite solid electrolyte layer; and a negative electrode layer laminated on the other side opposite to one side of the carbon / oxide-based composite solid electrolyte layer; wherein at least one of the positive electrode layer and the negative electrode layer may be manufactured by an electrode composition comprising a carbon / oxide-based composite solid electrolyte.

[0135] However, this is not limited to this, and any known layer structure and manufacturing method commonly used in the field to manufacture all-solid-state batteries may be applied by those skilled in the art with any design modifications.

[0137] Meanwhile, a battery module including the above-mentioned all-solid-state battery as a unit cell can be provided, and the battery module can be used as an energy source for medium to large devices requiring high temperature stability, long cycle characteristics, and high capacity characteristics.

[0138] Examples of the above medium-to-large devices include, but are not limited to, power tools that are powered by an electric motor; electric vehicles including electric vehicles (EV), hybrid electric vehicles (HEV), and plug-in hybrid electric vehicles (PHEV); electric two-wheeled vehicles including electric bicycles (E-bike) and electric scooters; electric golf carts; and power storage systems.

[0140] Hereinafter, the structure of the present invention and the resulting effects are to be explained in more detail through specific embodiments and comparative examples. However, these embodiments are intended to explain the present invention more specifically, and the scope of the present invention is not limited to these embodiments.

[0142] [Preparation Example 1: Preparation of Carbon / Oxide-Based Composite Solid Electrolyte]

[0143] 0.185g of LiOH, 30.519g of La(NO3), 20.308g of ZrO(NO3), 30.068g of Ga(NO3), 3.8g of citric acid, and 1g of acid-treated CNT were added to 120ml of diethylene glycol (DEG) as a solvent and stirred to prepare a mixed solution. 40ml of the mixed solution was placed in separate microwave Teflon vessels, and a precursor solution was prepared by microwave treatment at 250°C for 10 minutes at a power of 400W while stirring. Then, the precursor solution was centrifuged at 10,000 RPM for 1 hour to separate the precipitate and the supernatant. Subsequently, the obtained precipitate was placed in an alumina crucible and dried using an electric furnace at 250°C for 2 hours at a heating rate of 15°C / min to remove the remaining solvent (DEG). Then, the dried material was ground into powder using Agata mortar. The obtained powder was heat-treated at 360°C for 5 hours at a heating rate of 10°C / min in an air atmosphere, and then calcined at 900°C for 5 hours at a heating rate of 5°C / min in an inert atmosphere to produce carbon / oxide-based (CNT / LLZO) powder.

[0145] [Preparation Example 2]

[0146] Except for the details described below, a carbon / oxide-based (CNT / Ga-LLZO) composite solid electrolyte was prepared using the same method as in the aforementioned Preparation Example 1.

[0147] Instead of the acid-treated CNT used as the carbon material in Preparation Example 1, an untreated CNT was used.

[0149] [Preparation Example 3]

[0150] Except for the details described below, a carbon / oxide-based (CNT / Ga-LLZO) composite solid electrolyte was prepared using the same method as in the aforementioned Preparation Example 1.

[0151] It contained 0.7g of acid-treated CNT.

[0153] [Preparation Example 4]

[0154] Except for the details described below, a carbon / oxide-based (CNT / Ga-LLZO) composite solid electrolyte was prepared using the same method as in the aforementioned Preparation Example 1.

[0155] Microwave was applied at 300°C with a power of 350W for 10 minutes.

[0157] [Preparation Example 5]

[0158] Except for the details described below, a carbon / oxide-based (CNT / Ga-LLZO) composite solid electrolyte was prepared using the same method as in the aforementioned Preparation Example 1.

[0159] Carbon nanofibers (CNF) were used instead of CNTs as the carbon material.

[0161] [Preparation Example 6]

[0162] Except for the details described below, a carbon / oxide-based (CNT / Ga-LLZO) composite solid electrolyte was prepared using the same method as in the aforementioned Preparation Example 1.

[0163] Citric acid was not included in the preparation of the mixed solution.

[0165] [Preparation Example 7]

[0166] Except for the details described below, a carbon / oxide-based (CNT / Ga-LLZO) composite solid electrolyte was prepared using the same method as in the aforementioned Preparation Example 1.

[0167] The mixed solution contained 3.0g of citric acid.

[0169] [Preparation Example 8]

[0170] Except for the details described below, a carbon / oxide-based (CNT / Ga-LLZO) composite solid electrolyte was prepared using the same method as in the aforementioned Preparation Example 1.

[0171] The mixed solution contained 4.2g of citric acid.

[0173] [Preparation Example 9]

[0174] Except for the details described below, a carbon / oxide-based (CNT / Ga-LLZO) composite solid electrolyte was prepared using the same method as in the aforementioned Preparation Example 1.

[0175] Centrifugation of the precursor solution was performed at 9,000 RPM for 1 hour.

[0177] [Preparation Example 10]

[0178] Except for the details described below, a carbon / oxide-based (CNT / Ga-LLZO) composite solid electrolyte was prepared using the same method as in the aforementioned Preparation Example 1.

[0179] Centrifugation of the precursor solution was performed at 8,800 RPM for 1 hour.

[0181] [Preparation Example 11]

[0182] Except for the details described below, a carbon / oxide-based (CNT / Ga-LLZO) composite solid electrolyte was prepared using the same method as in the aforementioned Preparation Example 1.

[0183] Centrifugation of the precursor solution was performed at 10,000 RPM for 55 minutes.

[0185] [Preparation Example 12]

[0186] Except for the details described below, a carbon / oxide-based (CNT / Ga-LLZO) composite solid electrolyte was prepared using the same method as in the aforementioned Preparation Example 1.

[0187] Centrifugation of the precursor solution was performed at 8,800 RPM for 55 minutes.

[0189] [Preparation Example 13]

[0190] Except for the details described below, a carbon / oxide-based (CNT / Ga-LLZO) composite solid electrolyte was prepared using the same method as in the aforementioned Preparation Example 1.

[0191] Calcination was performed at 1,100°C for 7 hours in an inert atmosphere at a heating rate of 5°C / min, without following the calcination method of Preparation Example 1.

[0193] [Preparation Example 14]

[0194] Except for the details described below, a carbon / oxide-based (CNT / Ga-LLZO) composite solid electrolyte was prepared using the same method as in the aforementioned Preparation Example 1.

[0195] With respect to the total weight of the mixed solution of Preparation Example 1, guaiacol was further included at 0.05 wt%.

[0197] [Preparation Example 15]

[0198] Except for the details described below, a carbon / oxide-based (CNT / Ga-LLZO) composite solid electrolyte was prepared using the same method as in the aforementioned Preparation Example 1.

[0199] A mixture of organic germanium and grape skin extract powder was further included at 0.05% by weight relative to the total weight of the mixed solution of Preparation Example 1.

[0201] [Comparative Example 1]

[0202] Except for the details described below, a composite solid electrolyte was prepared in the same manner as in the aforementioned Preparation Example 1.

[0203] Instead of oxide components, the sulfide component Li10GeP2S 12 A carbon / sulfide-based (CNT / LGPS) composite solid electrolyte was prepared using (LGPS).

[0205] [Comparative Example 2]

[0206] Except for the details described below, a carbon / oxide-based (CNT / Ga-LLZO) composite solid electrolyte was prepared using the same method as in the aforementioned Preparation Example 1.

[0207] Microwave processing was not performed.

[0209] [Comparative Example 3]

[0210] Except for the details described below, a composite solid electrolyte was prepared in the same manner as in the aforementioned Preparation Example 1.

[0211] As in Preparation Example 1, a carbon / oxide-based (CNT / Ga-LLZO) composite was not formed, and an oxide-based (Ga-LLZO) solid electrolyte powder was prepared, then a CNT carbon material was prepared in a layered form, and then physically attached to be used.

[0213] <Evaluation Example 1: Characterization of Carbon / Oxide-Based Composite Solid Electrolytes>

[0214] Evaluation Example 1-1

[0215] The carbon / oxide-based (CNT / LLZO) composite electrolyte prepared according to Preparation Example 1 was analyzed by performing X-ray diffraction analysis (XRD) according to known techniques.

[0216] Figure 2 is a graph showing the X-ray diffraction (XRD) analysis results of the composite solid electrolyte prepared according to Preparation Example 1.

[0217] Referring to Fig. 2, it was confirmed by the peaks in the XRD graph that a carbon / oxide-based (CNT / LLZO) composite was formed according to the manufacturing method of Example 1.

[0219] Evaluation Example 1-2

[0220] For the carbon / oxide-based (CNT / LLZO) composite electrolyte prepared according to Example 1, Raman spectrum analysis was performed according to known techniques.

[0221] Figure 3 is a graph showing the results of the Raman spectrum analysis of the composite solid electrolyte prepared according to Example 1.

[0222] Referring to Figure 3, Li-O, La-O, Zr-O, and the D band (Disordered band) and G band (Graphitic band) peaks of CNT were identified in relation to the oxide (LLZO).

[0224] Evaluation Example 1-3

[0225] For the carbon / oxide-based (CNT / LLZO) composite electrolyte prepared according to Example 1, X-ray photoelectron spectroscopy (XPS) analysis was performed according to known techniques.

[0226] Figure 4 is a graph showing the X-ray photoelectron spectroscopy (XPS) analysis results of the composite solid electrolyte prepared according to Example 1.

[0227] Referring to Figure 4, Li 1s, La 3p, La 3d, La 4d, Zr 3p, Zr 3d, O 1s, and C 1s peaks of CNT were identified in relation to the oxide (LLZO).

[0229] Evaluation Example 1-4

[0230] The carbon / oxide-based (CNT / LLZO) composite electrolyte prepared according to Example 1 was analyzed using a scanning electron microscope (SEM) according to known techniques.

[0232] Evaluation Example 1-5

[0233] The carbon / oxide-based (CNT / LLZO) composite electrolyte prepared according to Example 1 was analyzed by energy dispersive X-ray spectroscopy (EDS) according to known techniques.

[0235] Figure 5 is a scanning electron microscope (SEM) analysis image of the composite solid electrolyte prepared according to Example 1, and Figure 6 is an energy dispersive X-ray spectroscopy (EDS) analysis image of the composite solid electrolyte prepared according to Example 1.

[0236] Referring to Figures 5 and 6 together, it was confirmed that the carbon / oxide-based (CNT / LLZO) composite prepared according to Example 1 has a structure in which oxide (LLZO) particles are mounted on and distributed on the CNT. In addition, the constituent elements of the CNT and oxide (LLZO) were identified as a result of analysis by energy dispersive X-ray spectroscopy (EDS).

[0238] Evaluation Example 1-6

[0239] The carbon / oxide-based (CNT / LLZO) composite electrolyte prepared according to Example 1 was analyzed by transmission electron microscopy (TEM) according to known techniques.

[0240] Figure 7 is a transmission electron microscope (TEM) analysis image of the composite solid electrolyte prepared according to Example 1.

[0241] Referring to Fig. 7, it was confirmed that the carbon / oxide-based (CNT / LLZO) composite prepared according to Example 1 has a structure in which nano-sized (less than 100 nm) LLZO particles are placed on and distributed on the CNT.

[0243] <Evaluation Example 2: Performance Evaluation of an All-Solid State Battery Containing a Carbon / Oxide-Based Composite Solid Electrolyte>

[0244] An all-solid-state battery of Example 1 was manufactured by sequentially stacking a positive electrode layer, a solid electrolyte layer, and a negative electrode layer according to conventional known techniques using an electrode composition based on a carbon / oxide-based composite solid electrolyte prepared according to the aforementioned Preparation Example 1. In the same manner, all-solid-state batteries of Examples 2 to 15 and Comparative Examples 1 to 3 were manufactured using electrode compositions based on the respective solid electrolytes of Preparation Examples 2 to 15 and Comparative Examples 1 to 3.

[0246] Meanwhile, a carbon / oxide-based (CNT / Ga-LLZO) composite solid electrolyte was prepared in the same manner as in Example 15, and then an isosorbide film layer (3% of the total thickness of the solid electrolyte layer) prepared according to known techniques was further formed on one side of the solid electrolyte layer to produce an all-solid-state battery of Example 16, and an all-solid-state battery of Example 17 was prepared in the same manner as in Example 16, except that the thickness of the isosorbide film layer was 5%.

[0247] Each all-solid-state battery was charged at 0.05 in a constant current-constant voltage mode to 4.25V at 60℃, and discharged to 3.0V at 0.05C, while measuring the initial charge capacity and initial discharge capacity. In addition, a life evaluation was conducted at 0.1C in the range of 3.7V to 4.2V. Table 1 below lists the number of cycles in which a short circuit occurred during the charge and discharge of the all-solid-state battery and the capacity retention rate at that time.

[0249] Initial efficiency (%) Capacity retention rate (% / 80 cycle) Example 1 91.2 89.8 Example 2 90.9 89.4 Example 3 90.5 88.5 Example 4 90.4 88.3 Example 5 89.6 87.3 Example 6 88.9 87.0 Example 7 90.8 88.9 Example 8 90.9 89.0 Example 9 90.2 88.4 Example 10 88.4 87.2 Example 11 89.2 88.9 Example 12 85.7 85.3 Example 13 89.0 88.6 Example 14 91.5 90.6 Example 15 92.6 91.5 Example 16 93.0 92.7 Example 17 92.8 92.0 Comparative Example 1 87.2 84.7 Comparative Example 2 86.3 84.9 Comparative Example 3 84.4 82.2

[0251] Referring to Table 1 above, it was confirmed that the all-solid-state batteries of the examples exhibited superior initial efficiency and capacity retention rates compared to the comparative examples. In particular, the all-solid-state batteries of Example 1 and Examples 14 to 17 demonstrated that the initial efficiency and capacity retention rates could be improved to a level of approximately 4 to 7% compared to the comparative examples. Thus, it can be confirmed that the carbon / oxide-based composite electrolyte prepared according to one embodiment of the present invention can exhibit a significant effect in improving the ionic resistance of the all-solid-state battery, particularly in improving battery life.

[0253] Optimal embodiments have been disclosed in the drawings and specification. Specific terms have been used herein, but are used only for the purpose of describing the invention and are not intended to limit the meaning or the scope of the invention as described in the claims. Therefore, those skilled in the art will understand that various modifications and equivalent alternative embodiments are possible therefrom. Accordingly, the true technical scope of protection of the invention should be determined by the technical spirit of the appended claims.

Claims

Claim 1 a) a step of preparing a mixed solution by adding 0.185g of LiOH, 30.519g of La(NO3), 20.308g of ZrO(NO3), 30.068g of Ga(NO3), 3.8g of citric acid, and 1g of acid-treated carbon nanotubes to 120ml of diethylene glycol (DEG) and stirring; b) a step of preparing a precursor solution by placing 40ml of the mixed solution into separate microwave Teflon vessels and microwave-treating them at 250°C for 10 minutes at a power of 400W while stirring; c) separating the precipitate and supernatant by centrifuging the precursor solution at 10,000 RPM for 1 hour, and drying at 250°C for 2 hours at a heating rate of 15°C / min to remove residual DEG, and A method for manufacturing a composite solid electrolyte for an all-solid-state battery, comprising: a step of preparing a precursor powder by grinding, and performing a first heat treatment of the precursor powder at 360°C for 5 hours at a heating rate of 10°C / min in an air atmosphere; and a step of performing a second calcination treatment of the first heat-treated powder at 900°C for 5 hours at a heating rate of 5°C / min under an inert atmosphere to prepare a carbon / oxide-based composite solid electrolyte powder having a composite structure in which gallium-doped lithium lanthanum zirconium oxide (Ga-LLZO) particles are distributed on the surface of acid-treated carbon nanotubes; wherein the gallium-doped lithium lanthanum zirconium oxide (Ga-LLZO) particles have a size of 100 nm or less. Claim 2 A composite solid electrolyte for an all-solid-state battery manufactured according to the method for manufacturing a composite solid electrolyte for an all-solid-state battery of claim 1, wherein the composite solid electrolyte for an all-solid-state battery is a carbon / oxide-based composite solid electrolyte forming a composite structure in which gallium-doped lithium lanthanum zirconium oxide (Ga-LLZO) particles are distributed on the surface of acid-treated carbon nanotubes, and wherein the gallium-doped lithium lanthanum zirconium oxide (Ga-LLZO) particles have a size of 100 nm or less. Claim 3 A solid-state battery comprising: a solid electrolyte layer including a composite solid electrolyte for a solid-state battery according to claim 2; a positive electrode layer laminated on one side of the solid electrolyte layer; and a negative electrode layer laminated on the other side opposite to one side of the solid electrolyte layer; wherein at least one of the positive electrode layer and the negative electrode layer is manufactured by an electrode composition including an active material and a composite solid electrolyte for a solid-state battery according to claim 2. Claim 4 delete Claim 5 delete Claim 6 delete Claim 7 delete Claim 8 delete Claim 9 delete Claim 10 delete Claim 11 delete Claim 12 delete

Citation Information

Patent Citations

  • Sulfide-based solid electrolyte composites, electrodes and all-solid-state battery using the same

    KR1020210073689A

  • LLZO solid electrolyte manufacturing method using microwave solvothermal synthesis method and LLZO solid electrolyte prepared thereby

    KR1020230028110A